DISCOVERY OF A NEW RETROGRADE TRANS-NEPTUNIAN OBJECT: HINT OF A COMMON ORBITAL PLANE FOR LOW SEMIMAJOR AXIS, HIGH-INCLINATION TNOs AND CENTAURS - Chen (陳英同), Ying-Tung; Lin (林省文), Hsing Wen; Holman, Matthew J.; Payne, Matthew J.; Fraser, Wesley C.; Lacerda, Pedro; Ip (葉永烜), Wing-Huen; Chen (陳文屏), Wen-Ping; Kudritzki, Rolf-Peter; Jedicke, Robert; Wainscoat, Richard J.; Tonry, John L.; et al. (Astrophysical journal. Letters, 2016)
ABSTRACT Although the majority of Centaurs are thought to have originated in the scattered disk, with the high-inclination members coming from the Oort cloud, the origin of the high-inclination component of trans-Neptunian objects (TNOs) remains uncertain. We report the discovery of a retrograde TNO, which we nickname "Niku," detected by the Pan-STARRS 1 Outer Solar System Survey. Our numerical integrations show that the orbital dynamics of Niku are very similar to that of 2008 KV42 (Drac), with a half-life of ∼500 Myr. Comparing similar high-inclination TNOs and Centaurs (q > 10 au, a < 100 au, and i > 60°), we find that these objects exhibit a surprising clustering of ascending node, and occupy a common orbital plane. This orbital configuration has high statistical significance: 3.8- . An unknown mechanism is required to explain the observed clustering. This discovery may provide a pathway to investigating a possible reservoir of high-inclination objects.